Molecular analysis of the interaction between the hematopoietic master transcription factors GATA-1 and PU.1. - Liew, C; Rand, K; Simpson, R; Yung, W; Mansfield, R; Crossley, M; Proetorius-Ibba, M; Nerlov, C; Poulsen, F; Mackay, J (2006)
GATA-1 and PU.1 are transcription factors that control erythroid and myeloid development, respectively. The two proteins have been shown to function in an antagonistic fashion, with GATA-1 repressing PU.1 activity during erythropoiesis and PU.1 repressing GATA-1 function during myelopoiesis. It has also become clear that this functional antagonism involves direct interactions between the two proteins. However, the molecular basis for these interactions is not known, and a number of inconsistencies exist in the literature. We have used a range of biophysical methods to define the molecular details of the GATA-1-PU.1 interaction. A combination of NMR titration data and extensive mutagenesis revealed that the PU.1-Ets domain and the GATA-1 C-terminal zinc finger (CF) form a low affinity interaction in which specific regions of each protein are implicated. Surprisingly, the interaction cannot be disrupted by single alanine substitution mutations, suggesting that binding is distributed over an extended interface. The C-terminal basic tail region of CF appears to be sufficient to mediate an interaction with PU.1-Ets, and neither acetylation nor phosphorylation of a peptide corresponding to this region disrupts binding, indicating that the interaction is not dominated by electrostatic interactions. The CF basic tail shares significant sequence homology with the PU.1 interacting motif from c-Jun, suggesting that GATA-1 and c-Jun might compete to bind PU.1. Taken together, our data provide a molecular perspective on the GATA-1-PU.1 interaction, resolving several issues in the existing data and providing insight into the mechanisms through which these two proteins combine to regulate blood development.